Correlation and Path Coefficient Analysis in Pomegranate (Punica granatum L.) - M M Mir (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
Studies were carried out to find out association between different characters and magnitude of association of different characters with gross fruit yield (kg/plant) in ten cultivars of pomegranate (Punica granatum L.) including one local check. Data revealed that genotypic correlation coefficients were higher than their corresponding phenotypic ones for most of the characters, implying an inherent relationship among them. Fruit weight, fruit diameter, fruit volume, juice content, fruit set and number of fruits/plant exhibited highly significant positive correlation. Among the characters studied, number of fruits/plant, fruit weight, fruit volume and fruit set recorded maximum positive direct effect towards gross fruit yield (kg/plant) at both the levels. This study revealed that both the number of fruits/plant and fruit weight could form a selection criterion for yield improvement in pomegranate.